Hatred out of love or love can be all-inclusive? Moderating effects of employee status and organizational affective commitment on the relationship between turnover intention and CWB - Liu, Xiaolang; Lu, Wenzhu; Liu, Shanshi; Qin, Chuanyan (Frontiers in Psychology, 2023)
Owing to the prevalence of flexible employment practices around the world and increasingly loose employee-organization relationships, employee turnover intention is gradually becoming normalized. This study aimed to examine the counterproductive work behaviors (CWB) of employees with turnover intention in the hybrid employment context. Drawing on the psychological contract process perspective, this research endeavored to examine whether higher turnover intention is associated with greater levels of CWB and to determine whether and how the association between turnover intention and CWB differs across temporary and permanent workers by considering organizational affective commitment. The results of analyzing 211 pairs of two-wave subordinate–supervisor matching data from a Chinese service company indicated that turnover intention is positively related to CWB, and the association is stronger for temporary workers than permanent ones. Such difference is caused by permanent workers’ higher organizational affective commitment than temporary workers. The findings’ implications for theory and research are provided in hybrid employment.